Challenges to Social Protection and Social Cohesion in Crisises in the Financial Sector - Terták, Elemér; Kovács, Levente (Public Finance Quarterly, 2020)
The entire world was reeling from the coronavirus epidemic (Covid-19) that hit also Europe in Spring 2020. Economic stakeholders were suddenly facing a great deal of uncertainty in their activities. Our paper attempts to explore the changes that have occurred in economic relations between individuals and on a broader scale in economic policy in the short time since the outbreak. In our analysis, we pay special attention to the social responsibility of the economic actors, as well as to the issue of savings. We show that, as a consequence of the epidemic, the European financial system had to face a complex economic crisis of such unexpected rapidity, which is without precedence since WWII. In our conclusions we point to the fact that in dealing with the state of emergency caused by the coronavirus, the banking system, apart from providing the traditional basic services, has also to shoulder a complex and adaptable role, which is indispensable also for the maintenance and strengthening of the social cohesion.